Local Clique Covering of Claw‐Free Graphs. Issue 1 (26th February 2015) - Javadi, Ramin; Maleki, Zeinab; Omoomi, Behnaz
Abstract: A k − clique covering of a simple graph G is a collection of cliques of G covering all the edges of G such that each vertex is contained in at most k cliques. The smallest k for which G admits a k − clique covering is called the local clique cover number of G and is denoted by lcc( G ). Local clique cover number can be viewed as the local counterpart of the clique cover number that is equal to the minimum total number of cliques covering all edges. In this article, several aspects of the local clique covering problem are studied and its relationships to other well‐known problems are discussed. In particular, it is proved that the local clique cover number of every claw‐free graph is at most c Δ / log Δ, where Δ is the maximum degree of the graph and c is a constant. It is also shown that the bound is tight, up to a constant factor. Moreover, regarding a conjecture by Chen et al. (Clique covering the edges of a locally cobipartite graph, Discrete Math 219(1–3)(2000), 17–26), we prove that the clique cover number of every connected claw‐free graph on n vertices with the minimum degree δ, is at most n + c δ 4 / 3 log 1 / 3 δ, where c is a constant.